Reinforcement of plasticized poly (lactic acid) with titanium dioxide nanofiller - Nur Ain Syafiqah Sudin (Tanjong Malim, 2021)
Reinforcement of plasticized poly (lactic acid) with titanium dioxide nanofiller by Nur Ain Syafiqah Sudin